Manajemen Pembelajaran Pendidikan Agama Islam Dalam Mewujudkan Karakter Religius Pada Peserta Didik - Muslim; Kartika, Ika; Kuswandi, Sony; Herawati, Silvi; Ropitasari, Anna (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research is motivated by the problem of lack of success in realizing religious education in educational institutions in particular or in community life in general, which is a problem between community understanding and religious behavior according to Islamic teachings. There are many incidents of brawls or student brawls that occur in big cities, students lose respect for their teachers, there are even students who beat their teachers if they don't go to class, apart from that, fighting tools and illegal drugs are also used. The aim of this research is to determine the management of Islamic religious education learning in realizing religious character in students. The research uses a qualitative method approach based on field research, research data is collected through observation, interviews, documentation, analysis, reduction, presentation and data verification. The results of the research show that the implementation of learning management was carried out well, the teachers were very enthusiastic in implementing religious culture at school. They always try their best to carry out activities based on religious culture, such as discipline in coming and teaching on time, reading the Koran well and correctly. Before the learning process takes place in the first lesson, accompany students in carrying out congregational prayers, and always maintain togetherness between teachers in carrying out their duties.